Neuronal Distribution Across the Cerebral Cortex of the Marmoset Monkey (Callithrix jacchus). (24th October 2018) - Atapour, Nafiseh; Majka, Piotr; Wolkowicz, Ianina H; Malamanova, Daria; Worthy, Katrina H; Rosa, Marcello G P
Abstract: Using stereological analysis of NeuN-stained sections, we investigated neuronal density and number of neurons per column throughout the marmoset cortex. Estimates of mean neuronal density encompassed a greater than 3-fold range, from >150 000 neurons/mm 3 in the primary visual cortex to ~50 000 neurons/mm 3 in the piriform complex. There was a trend for density to decrease from posterior to anterior cortex, but also local gradients, which resulted in a complex pattern; for example, in frontal, auditory, and somatosensory cortex neuronal density tended to increase towards anterior areas. Anterior cingulate, motor, premotor, insular, and ventral temporal areas were characterized by relatively low neuronal densities. Analysis across the depth of the cortex revealed greater laminar variation of neuronal density in occipital, parietal, and inferior temporal areas, in comparison with other regions. Moreover, differences between areas were more pronounced in the supragranular layers than in infragranular layers. Calculations of the number of neurons per unit column revealed a pattern that was distinct from that of neuronal density, including local peaks in the posterior parietal, superior temporal, precuneate, frontopolar, and temporopolar regions. These results suggest that neuronal distribution in adult cortex result from a complex interaction of developmental/ evolutionary determinants and functional requirements.